2018
DOI: 10.1248/bpb.b18-00486
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of the Hippocampus of Rats Experiencing Nicotine-Withdrawal Symptoms

Abstract: Nicotine-withdrawal symptoms have been indicated as a possible risk factor for neuropsychiatric events, such as depression and suicide, during use of smoking-cessation drugs. We aimed to investigate whether the results of the metabolomic analysis of the rat brain reflect nicotine-withdrawal symptoms. We also aimed to investigate the relative changes in each metabolite in the brains of rats with nicotine-withdrawal symptoms. We created rats experiencing nicotine-withdrawal symptoms through repeat administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Also, in rats, repeated injections with high doses of nicotine (6 mg/kg, s.c.; three injections per day × 7 days; salt or base form not specified) lead to 17% mortality but lower doses do not lead to mortality (1 and 3 mg/kg, s.c.; salt or base form not specified) (Liu et al, 2014). Similarly in other studies, repeated nicotine injections at lower doses (⩽2 mg/kg, s.c.; base) did not cause toxicity in mice or rats (Akimoto et al, 2018;Kota et al, 2007Kota et al, , 2008. The median lethal dose (LD50) of s.c. nicotine (base) is 16 mg/kg in mice and 25 mg/kg in rats (Table 2).…”
Section: Role Of Cotinine In the Development Of Nicotine Dependencementioning
confidence: 98%
See 1 more Smart Citation
“…Also, in rats, repeated injections with high doses of nicotine (6 mg/kg, s.c.; three injections per day × 7 days; salt or base form not specified) lead to 17% mortality but lower doses do not lead to mortality (1 and 3 mg/kg, s.c.; salt or base form not specified) (Liu et al, 2014). Similarly in other studies, repeated nicotine injections at lower doses (⩽2 mg/kg, s.c.; base) did not cause toxicity in mice or rats (Akimoto et al, 2018;Kota et al, 2007Kota et al, , 2008. The median lethal dose (LD50) of s.c. nicotine (base) is 16 mg/kg in mice and 25 mg/kg in rats (Table 2).…”
Section: Role Of Cotinine In the Development Of Nicotine Dependencementioning
confidence: 98%
“…Cessation of nicotine injections in adult female mice leads to somatic withdrawal signs but not anxiety-like behavior, hyperalgesia, or changes in locomotor activity (Kota et al, 2007(Kota et al, , 2008. In rats, cessation of nicotine injections produces decreased locomotor activity, anxiety, and depressive-like behavior (Akimoto et al, 2018;Pandey et al, 2001;Zaniewska et al, 2010). One study reported that during the first week of nicotine withdrawal, rats do not show changes in anxiety-like behavior (Morud et al, 2018).…”
Section: Role Of Cotinine In the Development Of Nicotine Dependencementioning
confidence: 99%
“…HRMAS NMR studies involving a variety of animal models of human diseases have been reported in recent publications. The utilized species have included rat, 35,42,55,90,94,[96][97][98][99][100][101][102][103] mouse, 29,48,50,[104][105][106][107][108][109][110][111][112][113][114][115][116] zebrafish, 34,117,118 sheep, 119,120 swine, 121,122 dog, 123 and chicken. 124 In addition to tumors, commonly the subject of HRMAS NMR publications, findings in disease models such as Alzheimer's disease, 105,113 heart transplantation, 99 obesity, 50 and stress, 101,102,110 have been reported.…”
Section: Metabolomics Studies Of Animal Modelsmentioning
confidence: 99%
“…Sufficient scientific evidence confirms that cigarettesmoking is associated with serious health including oral and systemic inflammatory conditions and malignancy [1][2][3]. Tobacco-smokers are usually reluctant to quit the habit as nicotine is addictive and its withdrawal elicits symptoms which encompass anxiety, psychological stress, and metabolic imbalances [4][5][6][7][8][9]. Nevertheless, those who are determined reduce or quit smoking rely on nicotine replacement therapies such as nicotine gums, lozenges, patches, and electronic nicotine delivery systems (ENDS) to replenish their bodily nicotine dependence and minimize the risk of nicotine withdrawal symptoms.…”
Section: Introductionmentioning
confidence: 99%